Total Synthesis of 1‐Hydroxytaxinine. Issue 35 (25th July 2019) - Imamura, Yusuke; Yoshioka, Shun; Nagatomo, Masanori; Inoue, Masayuki
Abstract: 1‐Hydroxytaxinine (1 ) is a cytotoxic taxane diterpenoid. Its central eight‐membered B‐ring possesses four oxygen‐functionalized centers (C1, C2, C9, and C10) and two quaternary carbon centers (C8 and C15), and is fused with six‐membered A‐ and C‐rings. The densely functionalized and intricately fused structure of 1 makes it a highly challenging synthetic target. Reported here is an efficient radical‐based strategy for assembling 1 from A‐ and C‐ring fragments. The A‐ring bearing an α‐alkoxyacyl telluride moiety underwent intermolecular coupling with the C‐ring fragment by a Et3 B/O2 ‐promoted decarbonylative radical formation. After construction of the C8‐quaternary stereocenter, a pinacol coupling reaction using a low‐valent titanium reagent formed the B‐ring with stereoselective installation of the C1, C2‐diol. Subsequent manipulations at the A‐ and C‐rings furnished 1 in 26 total steps. Abstract : Tax incentive : 1‐Hydroxytaxinine, a cytotoxic taxane diterpenoid, possesses a highly oxygenated 6/8/6‐membered ring (ABC‐ring) system. Decarbonylative intermolecular radical coupling and low‐valent titanium promoted intramolecular radical cyclization were employed as the two key reactions to annulate the B‐ring from A‐ and C‐ring fragments. Subsequent manipulations at the A‐ and C‐rings furnished 1‐hydroxytaxinine in a total of 26 steps.